Ultrasound-assisted green solvent extraction of high-added value compounds from microalgae Nannochloropsis spp. (December 2015) - Parniakov, O.; Apicella, E.; Koubaa, M.; Barba, F.J.; Grimi, N.; Lebovka, N.; Pataro, G.; Ferrari, G.; Vorobiev, E.
Highlights: Ultrasound treatment (UST) increases recovery of bioactive compounds. UST combined with binary mixture of solvents led to the maximum recovery. Degradation of chlorophylls was observed at long time of UST. No synergy in recovery was observed between UST and temperature increase. Abstract: The aim of this work was to investigate ultrasound (US)-assisted green solvent extraction of valuable compounds from the microalgae Nannochloropsis spp. Individual green solvents (water, ethanol (EtOH), dimethyl sulfoxide (DMSO)) and binary mixture of solvents (water-DMSO and water-EtOH) were used for the extraction procedures. Maximum total phenolic compounds yield ( Yp  ≈ 0.33) was obtained after US pre-treatment ( W  = 400 W, 15 min), being almost 5-folds higher compared to that found for the untreated samples and aqueous extraction ( Yp  ≈ 0.06). The highest yield of total chlorophylls ( Yc  ≈ 0.043) was obtained after US ( W  = 400 W, 7.5 min), being more than 9-folds higher than those obtained for the untreated samples and aqueous extraction ( Yc  ≈ 0.004). The recovery efficiency decreased as DMSO > EtOH > H2 O. The optimal conditions to recover phenolic compounds and chlorophylls from microalgae were obtained after US pre-treatment (400 W, 5 min), binary mixtures of solvents (water-DMSO and water-EtOH) at 25–30%, and microalgae concentration of 10%.